Knowledge, Attitudes, and Treatment Seeking Behavior about Malaria and Its Control among Patients Attending Fever Clinic in a Tertiary Care Hospital of Eastern India - Gupta, Chandra Narayan; Maji, Kausik; Mukherjee, Shatavisa; Saha Roy, Sukalyan; Sen, Sukanta (International Journal of Innovative Research in Medical Science, 2018)
Background: Malaria continues to be a serious public health problem in South-East Asia including India. We assessed knowledge, attitudes, recognition of signs and symptoms and treatment seeking behavior about malaria and its control in patients with fever attending fever clinic at tertiary care hospital, Kolkata, India. Material and Methods: A cross-sectional questionnaire based survey was done in patients attending fever clinic. A total of (n = 68) patients with fever were interviewed using standardized questionnaire. Results: A total of 68 subjects were interviewed, including 19 (27.94%) females and 49 (72.06%) males. Mean age was 39.8 ± 17.2 years (18–78). About 5 (7.35%) were illiterate. All of the study participants had heard of malaria. The most common response on the source of information regarding malaria was radio (32.35%) followed by TV (29.41%) and friends (26.47%). About 52.94% replied that malaria can be prevented. Approx 39.7% subjects informed that fever plus chills are the most clinical features of malaria, followed by (fever+ chills + bodyache) in 32.35% cases. The most common response on the source of information regarding malaria transmission by mosquito bite was in 92.65% cases. Knowledge about breeding places of mosquitoes was informed as dirty stagnant water by 47.06%. Conclusions: Greater awareness about malaria and undertaking a broader range of preventive actions for malaria influence appropriate treatment-seeking behaviour. This study was conducted to understand issues, which can be an important step towards developing strategies, aimed at controlling malaria. The positive attitudes and practices in relation to personal protection and prevention measures against malaria require marked improvement.